CONCERNS, CANNABIS AND COGNITION - Shaughnessy, Michael F.; Sanchez, Andrew; Johnson, Aaron; Holin, Lyle Marty; Rucker, Lela (Acta Scientiae et Intellectus, 2024)
With the legalization of marijuana for medicinal and also recreational benefits, there is much concerns about second hand smoke, children and adolescents observing and modeling their behavior upon seeing their parents and elders utilize marijuana, and even concerns about the impact of cannabis on children in utero. This paper cursorily reviews some of the most recent research and concerns relative to the use of marijuana and its impact on others.